DEVELOPMENT OF THE SCHOOL AS MULTIFUNCTIONAL COMMUNITY RESOURSE IN LATVIA: OPPORTUNITIES AND CHALLENGES - Tūna, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In the context of rapid changes in the society schools face the problem of how to provide services in a way which promotes lifelong learning, social cohesion and sustainable development for individuals and communities while being efficient and accountable. The impact of the financial crises, declining number of students and uncertainty about rural development in general has put small rural schools in Latvia in a challenging situation. Since 2009 the initiative has been implemented to support schools to develop into multifunctional community centres by expanding their functions and reconsidering their role in local communities. The results of the study conducted on the bases of this initiative demonstrate significant potential of community school approach and also reveal challenges in understanding and implementing such approach.